2011
DOI: 10.1084/jem.20110845
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the neutrophil-associated high-affinity receptor for IgE in the pathogenesis of experimental cerebral malaria

Abstract: FcεR1-expressing neutrophils accumulate in the brain of mice infected with Plasmodium berghei (PbANKA) and promote the development of experimental cerebral malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 51 publications
1
91
0
Order By: Relevance
“…Therefore, as seen with allergy, not all patients should have the same probability of developing SM. This consideration could help to reconcile our results with those obtained in a murine model whose allergic susceptibility remains to be determined (32). Further studies are required to identify the determinants of basophil sensitization, such as mosquito bites (D. Aldebert, unpublished data), allergen sensitization, or helminth coinfection, in areas of malaria endemicity, but this new field of investigation has already provided additional keys for a better understanding of malaria immunopathogenesis.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, as seen with allergy, not all patients should have the same probability of developing SM. This consideration could help to reconcile our results with those obtained in a murine model whose allergic susceptibility remains to be determined (32). Further studies are required to identify the determinants of basophil sensitization, such as mosquito bites (D. Aldebert, unpublished data), allergen sensitization, or helminth coinfection, in areas of malaria endemicity, but this new field of investigation has already provided additional keys for a better understanding of malaria immunopathogenesis.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, Porcherie et al reported that mast cells and basophils are not involved in experimental cerebral malaria after infection with P. berghei ANKA (33). Based on these findings and the known abilities of IL-3 to influence mast cell and basophil growth and function, the role of endogenous IL-3 in regulating the numbers of splenic mast cells during P. berghei NK65 infection were examined.…”
Section: Resultsmentioning
confidence: 99%
“…(35)(36)(37)(38)(39). Moreover, recent studies revealed a role for inflammatory monocytes, in the recruitment of CD8 + T cells to the brain of P. berghei ANKA-infected mice (40).…”
Section: Discussionmentioning
confidence: 99%